The torn veil: Matthew's exposition of the death of Jesus - Gurtner, Daniel M. (Society for New Testament Studies monograph series, 2007)
In this 2006 text, Daniel M. Gurtner examines the meaning of the rending of the veil at the death of Jesus in Matthew 27:51a by considering the functions of the veil in the Old Testament and its symbolism in Second Temple and Rabbinic Judaism. Gurtner incorporates these elements into a compositional exegesis of the rending text in Matthew. He concludes that the rending of the veil is an apocalyptic assertion like the opening of heaven revealing, in part, end-time images drawn from Ezekiel 37. Moreover, when the veil is torn Matthew depicts the cessation of its function, articulating the atoning role of Christ's death which gives access to God not simply in the sense of entering the Holy of Holies (as in Hebrews), but in trademark Matthean Emmanuel Christology: 'God with us'. This underscores the significance of Jesus' atoning death in the first gospel.